Savings and inflation - a panel threshold model approach - Ferreira, Mariana Miguel dos Reis (2017)
This research investigates the impact of inflation on savings through a panel of 42 countries observed annually between 1995 and 2014. A panel threshold model approach is followed, being one-year lagged inflation the threshold variable and gross savings the dependent one. Findings suggest that inflation has a positive impact on gross savings, particularly at lower levels of inflation. The robustness tests conducted led to conclude that the model does not hold for less developed economies where savings are not so correlated with the inflation level as it is among developed economies.